Thermal performance of semitransparent CdTe BIPV window at temperate climate. (1st January 2020) - Alrashidi, Hameed; Ghosh, Aritra; Issa, Walid; Sellami, Nazmi; Mallick, Tapas.K.; Sundaram, Senthilarasu
Highlights: Test cell characterization was performed to evaluate thermal performance of CdTe BIPV glazing. Visible transmission of this CdTe BIPV window is 25%. Overall heat transfer coefficient of 2.7 W/m 2 K was found for CdTe BIPV glazing. Abstract: Semi-transparent photovoltaic (PV) technology is attractive for building-integrated photovoltaics (BIPV) due to its ability to lower the admitted solar heat gain, to control the penetrating daylight and to generate onsite benevolent direct current power. In this work, semi-transparent cadmium telluride (CdTe) based BIPV as window was experimentally characterized using outdoor test cell in temperate UK climate. Spectral measurement confirmed its 25% visible transmission and 12% solar transmission. Thermal transmission and solar heat gain coefficient were calculated from measured thermal data. Overall heat transfer coefficient ( U -value) of 2.7 W/m 2 K was found for outdoor and indoor characterization of CdTe BIPV window. A comparison with single glazed window has been produced emphasis its feasibility for Facade buildings.